The Relationship between Intimate Friendship and Online Self-Disclosure in Second Instagram Account Users - Nabila, Salsa; Nurhabibah; Resha Yuwanda (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The phenomenon of second Instagram accounts in early adulthood as a place to explore oneself freely online. Having a second Instagram account allows users to carry out online self-disclosure to friends who have intimate friendships. The aim of this research is to determine the relationship between intimate friendship and online self-disclosure among second Instagram account users in early adulthood. This research uses a quantitative approach with a correlational design. The sampling technique used is accidental sampling. The sample in this study was 274 respondents consisting of 136 women and 138 men. Based on the results of the product moment correlation test between the intimate friendship variable and online self-disclosure disclosure for second Instagram account users, it shows that the correlation coefficient value is 0.138 with a significance of 0.023 (p<0.05) so it can be concluded that there is a significant positive relationship between intimate friendship and online self-disclosure for second Instagram account users. The higher the intimate friendship, the higher the online self-disclosure of second Instagram account users.